Stilasi Ragam Hias Rumah Gadang untuk Produk Playset Rumah Adat - Jaya, Brian Kurniawan (Keluwih: Jurnal Sains dan Teknologi, 2022)
Abstract—The Minangkabau tribe is part of West Sumatra. This tribe has a concept of living about human behavior that reflects on nature, humans, and society, as well as humans and their Creator. Similar concepts are also expressed in the decorations found in the traditional building of the Gadang house. Follow-up to the preservation of this culture is very important, so that the noble values ​​that shape the character of the nation can be disseminated. Law No. 5 of 2017 describes the Advancement of Culture which has regulated the idea of ​​protecting, utilizing, and developing culture and the importance of introducing adat as community knowledge. Three of the objects of its promotion are customs, traditional knowledge, and folk games. The qualitative method consists of interviews, observations and documentation which is complemented by a literacy study as an initial stage followed by the process of stylizing the ornaments of the Gadang house. The results of the ornament stylization have the philosophy and values ​​of the Minangkabau community and are applied to the design of traditional house playset products, to introduce culture to the wider community. Keywords: minangkabau tribe, playset, traditional house, stylization Abstrak—Suku Minangkabau merupakan bagian dari Sumatera Barat. Suku ini memiliki konsep pandangan hidup tentang perilaku manusia yang berefleksi terhadap alam, manusia, dan masyarakat, serta manusia dengan sang Pencipta. Konsep-konsep serupa juga dituangkan dalam ragam hias yang terdapat pada bangunan adat rumah Gadang. Tindak lanjut terhadap pelestarian budaya ini sangatlah penting, agar nilai luhur yang membentuk karakter bangsa dapat disebarluaskan. UU no 5 tahun 2017 memaparkan tentang Pemajuan Kebudayaan yang telah mengatur gagasan untuk melindungi, memanfaatkan, dan mengembangkan kebudayaan dan pentingnya memperkenalkan adat sebagai pengetahuan bermasyarakat. Tiga diantara objek-objek pemajuannya adalah adat istiadat, pengetahuan tradisional, dan permainan rakyat. Metode kualitatif yang terdiri dari wawancara, observasi serta dokumentasi yang dilengkapi dengan studi literasi sebagai tahapan awal yang diikuti dengan proses stilasi ragam hias dari rumah Gadang. Hasil stilasi ornamen tersebut memiliki filosofi maupun nilai-nilai luhur dari masyarakat Minangkabau dan diterapkan pada perancangan produk playset rumah adat, sebagai wadah memperkenalkan kebudayaan kepada masyarakat luas. Kata kunci: suku minangkabau, permainan, rumah adat, stilasi